Bio-Delignification Pre-Treatment Of Lignocellulosic Biomass, Oil Palm Frond (Opf) And Empty Fruit Bunch (Efb) A Review In Biofuels And Biogas Processing - Fadzil, Muhammad Luqman Mohd (Universiti Sains Malaysia, 2021)
This study focuses in determining results in relation to three review objectives. Firstly is regarding to lignocellulosic biomass characteristics for both oil palm frond (OPF) and empty fruit bunch (EFB). Afterwards is type of pre-treatment available and their comparison between each other in terms of hydrolysis process of lignocellulosic biomass. Lastly is mechanism for bio-delignification of OPF and EFB using by using fungi. The dissertation is carried out in a systematic literature format (SLR). Lignocellulosic biomass characteristics is determined by signifying the structural content in agricultural biomass for instance cellulose, hemicellulose and lignin composition. Effect of hydrolysis process is determined from past studies where it stated as lignin removal percentages or hydrolysis yield. Mechanism involved in bio-delignification of EFB and OPF through the use fungi (white-rot fungi) is divided into two, selective delignification and non-selective delignification.